1991
DOI: 10.1084/jem.174.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CD8 that affect interactions with HLA class I and monoclonal anti-CD8 antibodies.

Abstract: SummaryThe T cell co-receptor, CD8, binds to the 0 domain of HLA class I (Salter, R .D., R .J. Benjamin, P.K . Wesley, S .E. Buxton, T.P.J . Garrett, C. Clayberger, A.M . Krensky, A .M . Norman, D.R. Littman, and P Parham . 1990. Nature (Lond]. 345 :41; Connolly, J.M ., TA. Potter, E.M. Wormstall, and TH . Hansen. 1988 . J. ExpL Med. 168 :325 ; and Potter, TA., TV. Rajan, R.F. Dick II, and J .A . Bluestone . 1989 . Natur e (Lond.j. 337 :73). To identify regions of CD8 that are important for binding to HLA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Human CD8␣ lysine (58) within the CDR2 loop is critical for the electrostatic-based association with the ␣3 acidic loop of HLA. Mutational analysis of the human CD8␣ CDRs resulted in Ͼ70 -80% (CDR1) and 50 -65% (CDR2) reduction in MHC class I binding (6). Moreover, introduction of negatively charged residues within CDR1 abrogated HLA binding, presumably via electrostatic repulsion with the HLA ␣3 acidic loop.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human CD8␣ lysine (58) within the CDR2 loop is critical for the electrostatic-based association with the ␣3 acidic loop of HLA. Mutational analysis of the human CD8␣ CDRs resulted in Ͼ70 -80% (CDR1) and 50 -65% (CDR2) reduction in MHC class I binding (6). Moreover, introduction of negatively charged residues within CDR1 abrogated HLA binding, presumably via electrostatic repulsion with the HLA ␣3 acidic loop.…”
Section: Discussionmentioning
confidence: 99%
“…Base pairs refer to positions within Onmy-CD8␣ cDNA (AF178053). Two sense primers (E1S, 5Ј-GAGCTT GAACGTGTTGCTGT-3Ј; bp [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and nested ES2, 5Ј-AGAGGGTG GAGATCACTTGT-3Ј; bp 126 -145) based on a putative V region cDNA were used in conjunction with an anchored T7 primer (3Ј region of the pCMV-Zap Express MCS) to amplify (30 cycles consisting of 94°C for 10 s, 55°C for 30 s, and 72°C for 1 min) the full-length cDNAs from the trout thymocyte cDNA library. Products were cloned into pBlunt (Invitrogen) and sequenced.…”
Section: Cdna Cloning and Genomic Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent analysis of genomic DNA from wild-type and homozygous mutant rats confirmed a T3 C transition that encoded a substitution of a proline residue (CCA) for a highly conserved serine residue (TCA) at amino acid position 94, which is adjacent to the distal cysteine residue that forms the single disulfide loop (7) (Figure 1). This mutation would be expected to profoundly disrupt the formation of the disulfide loop and the folding of the CD8␣ chain, since Pro cannot assume the bond angles that Ser assumes in accommodating disulfide bond formation by the adjacent Cys 93 and since this substitution is predicted to cause the loss of an H-bond between ␤ strands C and F (23,24). A much more conservative missense mutation (Gly3 Ser) in the human CD8A gene at the position 5 residues N-terminal of this Ser was reported to produce the absence of CD8␣ expression, leading to immunodeficiency in a homozygous subject (25).…”
Section: Induction Of a Heritable Cd8␣-null Mutationmentioning
confidence: 99%
“…Both the CD8 ␣-and ␤-chains are composed of a single extracellular Ig superfamily (IgSF) 3 variable (V) domain, a membrane-proximal hinge (H) region, a transmembrane domain (TM), and a cytoplasmic tail (CY). Biochemical and structural studies have shown that the Ig V domain of CD8␣, in conjunction with that of CD8␤, interacts with MHC class I molecules, thereby allowing the CD8 molecule to function as a coreceptor of the T cell Ag receptor (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%